‘Security’ and private governance in São Paulo’s corporate centrality frontier - De Biaggi, Gabriella DD (Urban studies (Edinburgh, Scotland), 2024)
In the last half-century, the ‘centre–periphery’ model has become insufficient to describe the increasingly fragmented and multicentric Latin American metropolises. Frontiers between central and peripheral areas are shifting, in part, due to the emergence of new corporate centralities, usually located outside historical city centres and heavily equipped with private ‘security’ agents and devices. By examining the evolving governing practices taking place in and around the dynamic frontier of a business centrality in São Paulo, Brazil, this article discusses the connections between the transformation in centre–periphery relations and the reworking of prior forms of socio-spatial control since the ‘security’ turn of the 1990s. More specifically, it explores the effects of the production of securitised corporate centralities on the racialised differential governance of urban space. For this purpose, the article draws from empirical work involving fieldwork, interviews with public and private ‘security’ agents, the observation of meetings of the local Public Security Community Council (CONSEG), and the analysis of police statistics. In sum, the argument presented here is that the evolution of segregation mechanisms and governing practices in Latin-American metropolises reproduces centre–periphery relations under new spatial configurations, and increases the capacity of private agents to subject urban space to their own rules and regulations.